Perception of invulnerability, engaging in risky behaviors and life satisfaction among high school students - Milić, Marija, psihologinja (Array, 2019)
A sense of invulnerability is commonly associated only with adolescents’ risk behaviors, but according to some developmental theories, it is also an adaptive response to developmental tasks that occur during that period of life. The objective of this paper was to explore two aspects of the sense of invulnerability (physical and psychological) on a sample of high school students. More specifically, the relationship between physical and psychological invulnerability in terms of engagement in risky behaviors (cigarette use) on the one hand and indicators of subjective wellbeing (life satisfaction) on the other was explored. The data from 297 adolescents aged 16 to 20 years (M = 17.33; SD = 0.834; 54.2% girls) were analyzed. The study found that boys’ assessment of physical and psychological invulnerability was higher in comparison to girls’ assessment.Smokers rated their physical invulnerability higher than adolescents who had quit smoking, who had only tried smoking and those who had never smoked. While physical invulnerability was not associated with life assessments in most domains of life satisfaction, psychological was positively associated with all domains as well as general life satisfaction. The findings also showed that assessing psychological invulnerability contributed more to explaining life satisfaction than assessing physical invulnerability, whereas physical invulnerability was a significant predictor of smoking frequency among adolescents. The results of this study indicate the significance and importance of both domains of invulnerability in adolescence.